Single cell analysis : contemporary research and clinical applications - Robinson, J. Paul; Cossarizza, Andrea, 1958- (Springer, 2017)
This book highlights the current state of the art in single cell analysis, an area that involves many fields of science - from clinical hematology, functional analysis and drug screening, to platelet and microparticle analysis, marine biology and fundamental cancer research. This book brings together an eclectic group of current applications, all of which have a significant impact on our current state of knowledge. The authors of these chapters are all pioneering researchers in the field of single cell analysis. The book will not only appeal to those readers more focused on clinical applications, but also those interested in highly technical aspects of the technologies. All of the technologies identified utilize unique applications of photon detection systems.
Keywords: Flow cytometry.; elektronické knihy; electronic books